Programming with the KIBO Robotics Kit in Preschool Classrooms. Issue 3 (2nd July 2016) - Elkin, Mollie; Sullivan, Amanda; Bers, Marina Umaschi
ABSTRACT: KIBO is a developmentally appropriate robotics kit for young children that is programmed using interlocking wooden blocks; no screens or keyboards are required. This study describes a pilot KIBO robotics curriculum at an urban public preschool in Rhode Island and presents data collected on children's knowledge of foundational programming concepts after completing the curriculum. The curriculum was designed to integrate music, literacy, and design with engineering and robotics. Children ( N = 64) from seven preschool classrooms, ranging in age from 3 to 5, participated in the study. Findings indicated that children as young as age 3 could create syntactically correct programs for the KIBO robot, although older preschoolers (closer to age 5) performed better than younger preschoolers on a standardized programming task. Additionally, all students generally performed better on the programming tasks that required them to manipulate less programming instructions. Implications for designing developmentally appropriate curriculum and scaffolding for young children are addressed.